Redefining and revisiting cost estimates of routine ART care in Zambia: an analysis of ten clinics. Issue 2 (17th February 2020) - Tucker, Austin; Tembo, Tannia; Tampi, Radhika P; Mutale, Jacob; Mukumba‐Mwenechanya, Mpande; Sharma, Anjali; Dowdy, David W; Moore, Carolyn B; Geng, Elvin; Holmes, Charles B; Sikazwe, Izukanji; Sohn, Hojoon
Abstract: Introduction: Accurate costing is key for programme planning and policy implementation. Since 2011, there have been major changes in eligibility criteria and treatment regimens with price reductions in ART drugs, programmatic changes resulting in clinical task‐shifting and decentralization of ART delivery to peripheral health centres making existing evidence on ART care costs in Zambia out‐of‐date. As decision makers consider further changes in ART service delivery, it is important to understand the current drivers of costs for ART care. This study provides updates on costs of ART services for HIV‐positive patients in Zambia. Methods: We evaluated costs, assessed from the health systems perspective and expressed in 2016 USD, based on an activity‐based costing framework using both top‐down and bottom‐up methods with an assessment of process and capacity. We collected primary site‐level costs and resource utilization data from government documents, patient chart reviews and time‐and‐motion studies conducted in 10 purposively selected ART clinics. Results: The cost of providing ART varied considerably among the ten clinics. The average per‐patient annual cost of ART service was 116.69 (range: 59.38 to 145.62) using a bottom‐up method and 130.32 (range: 94.02 to 162.64) using a top‐down method. ART drug costs were the main cost driver (67% to 7% of all costs) and are highly sensitive to the types of patient included in the analysis (long‐term vs. all ART patients, including those recently initiated) and the data sources used (facility vs. patient level). Missing capacity costs made up 57% of the total difference between the top‐down and bottom‐up estimates. Variability in cost across the ten clinics was associated with operational characteristics. Conclusions: Real‐world costs of current routine ART services in Zambia are considerably lower than previously reported estimates and sensitive to operational factors and methods used. We recommend collection and monitoring of resource use and capacity data to periodically update cost estimates.